HIGH-ENERGY NANOCRYSTALLINE Nd-Fe-B MAGNETIC MATERIALS – SYNTHESIS, CHARACTERIZATION, APPLICATION - N. Talijan (Journal of Engineering & Processing Management, 2010)
One of the most widely used high-energy nanocrystalline permanent magnetic materials are Nd-Fe-B alloys. Current R&D of Nd-Fe-B magnets is focused on three major topics: increase of magnetic energy, improvement of corrosion resistance and reduction of rare-earth content as a way of decreasing prices of final magnetic material with still significant magnetic energy. Utilizing the high sensitivity of microstructure and magnetic properties of Nd-Fe-B alloys to the Nd content, three distinctive types of nanocrystalline alloys have been developed: stoichiometric magnets, Ndrich (decoupled magnets) and magnets with reduced Nd content (nanocomposite magnets). In the presented paper a brief overview of each type of Nd-Fe-B alloy is given, processing methods are outlined and several high technology application examples are presented. Based on experimental results obtained using modern high resolution characterization techniques optimal processing conditions for the selected synthesis method are presented. Trends and challenges in future R&D of magnetic nanomaterials are discussed.
Keywords: nanostructured magnetic materials; Nd-Fe-B alloys; magnetic properties